(untitled) (Hoboken, N.J, 2006)
This text provides an excellent balance of theory and application that enables you to deploy powerful algorithms, frameworks, and methodologies to solve complex optimization problems in a diverse range of industries. Each chapter is written by leading experts in the fields of parallel and distributed optimization. Collectively, the contributions serve as a complete reference to the field of combinatorial optimization, including details and findings of recent and ongoing investigations.
Keywords: Electronic data processing,Combinatorial optimization,Xử lý dữ liệu điện tử,Tối ưu hóa tổ hợp; Distributed processing,Xử lý phân tán